Epidemiology of Haemophilus parasuis isolates from pigs in China using serotyping, antimicrobial susceptibility, biofilm formation and ERIC-PCR genotyping - Zhao, Yongda (PeerJ, 2018)
BACKGROUND: Haemophilus parasuis is a commensal organism of the upper respiratory tract of healthy pigs and causes high morbidity and mortality in piglets. The aim of this study was to investigate the epidemiology of H. parasuis in China from 2014 to 2017. METHODS: We characterized 143 H. parasuis isolates by serotyping, antimicrobial susceptibility, biofilm formation and with enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) assays. RESULTS: Serotyping revealed serovar 5 as the most prevalent (26.6%) followed by serovars 4 (22.4%), 7 (9.1 %), 13 (6.3%), 12 (5.6 %), and non-typeable (8.4%). In a panel of 23 antimicrobials, the minimum inhibitory concentration 50% (MIC(50)) were in the range of 0.25–16 μg/mL and MIC(90) were 2–>512 μg/mL. A total of 99 isolates of H. parasuis (69.2%) were able to form biofilms and 59.6% (59/99) performed weak biofilm-forming ability. ERIC-PCR revealed a very heterogeneous pattern with 87 clusters. DISCUSSION: These H. parasuis isolates showed a high serovar and genotypic lineage diversity, different abilities to form biofilms and a high degree of genetic diversity. Biofilm formation was related to antimicrobial susceptibility but there were no statistically significant associations between the antimicrobial susceptibility and either the serovars or the ERIC-PCR clusters. This study showed a high prevalence of high-MIC H. parasuis strains and suggests the need for a continuous surveillance of clinical isolates of H. parasuis.